FROM TIMELINE TO PUBLIC SPHERE: SOCIAL MEDIA NEWS CONSUMPTION AND POLITICAL EXPRESSION AMONG YOUTH - Prawira, R. Yogie; Khotijah, Nifta Alifatul; Sanofi, Zuhairi; Mazid, Sukron (Universitas Padjadjaran, 2025)
The growing prevalence of social media as a source of news consumption has significant implications for political expression among youth. This study examines the impact of news consumption on political expression among young social media users in Indonesia. Using a quantitative approach, data were collected from 228 respondents through a structured questionnaire and analyzed using linear regression. The result suggested that news consumption on social media has a positive effect on users' political expression, although with a relatively small effect size (7.3%). It affirms the relevance of the relationship between news consumption on social media, but the small effect indicates an anomaly. There are some possibilities that may become barriers, such as the existence of the ITE Law which regulates the use of information technology, political efficacy, communication competence, social environment, and individual motivation in shaping political expression. The influence of these factors may differ across various social media platforms and contexts, necessitating further comprehensive research to fully comprehend political expression in the digital era. The diversity of platforms and different contexts are important aspects for conducting more in-depth research to obtain a comprehensive understanding of political expression in different digital eras. Limitations of this study include an unrepresentative sample, and potential bias in self-reported measurement of political expression. Future research is recommended to employ more representative samples and integrate content analysis with questionnaires to obtain more accurate data on this phenomenon.